If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) = 2(x + 5) Reorder the terms: 4(2 + x) = 2(x + 5) (2 * 4 + x * 4) = 2(x + 5) (8 + 4x) = 2(x + 5) Reorder the terms: 8 + 4x = 2(5 + x) 8 + 4x = (5 * 2 + x * 2) 8 + 4x = (10 + 2x) Solving 8 + 4x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + 4x + -2x = 10 + 2x + -2x Combine like terms: 4x + -2x = 2x 8 + 2x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + 2x = 10 + 0 8 + 2x = 10 Add '-8' to each side of the equation. 8 + -8 + 2x = 10 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 10 + -8 2x = 10 + -8 Combine like terms: 10 + -8 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| (10*9+5*5)=x | | 5u-7u=-8 | | 5a^2-8a-31=-10 | | 51ln(1-x)=ln(1-46x) | | (10*8+5*5)*28=x | | -28+7m=-4(4m+7) | | -1=-3/4(m+7) | | x^3-4xy=0 | | -18-11x=36 | | 100-128x=2 | | 8(x-9)=8x+-72 | | 7(6n+7)+8=-195 | | 2x-2a+b=3x+a | | -8(-5-2x)=168 | | 6x+12y-15z= | | 2(2.66)+2= | | s^2-22=112 | | -45-(-59)= | | 8=.35(c+6) | | 10-6(8x-2)=9x-(3+4x) | | 4x+2(7+6x)=142 | | 15(x+2)-1=2 | | 6x^4-16=0 | | 3(x-4)=5x+9 | | u^2-4= | | 5x+27=37 | | 5(3+7r)=-39+8r | | 9x+2=5x-7 | | 10n=63 | | 3y-4y-2y= | | 9j-3=-6(j-7) | | (x+1)*4+1=7 |